Criminality among Stockholm mental patients - Lindqvist, Per (The British journal of criminology, 1999)
Comments on the article of H. Belfrage (1998) entitled `A ten-year follow-up of criminality in Stockholm mental patients,' on the alleged errors in the study conducted by Lindqvist and Allebeck (1990). Failure of Belfrage to present an epidemiological study including lack of age and gender stratified in the comparison group; Contrast between the study of Belfrage and Linqvist et al